THE BUILDING OF ONLINE PERSONAL BRANDING - Avinash Pawar; Mia Kusmiati; Sri Sundari (Universitas Indonesia Membangun (Inaba), 2022)
Personal branding is the process of branding people and their work, and its motivation is different from awareness management and impression management. Providing benefits and brand equity associated with a particular individual is simply planned. Branding efforts usually require extensive financial support to make progress in order to raise brand awareness and soon afterwards to increase brand credibility. With its ideological and innovative structure, online networking gives the general public the opportunity to develop as a brand in a reasonably crude and productive way. Online personal branding refers to an approach that conveys the superior qualities of an individual in the online phase, helping to achieve professional goals with social aspirations, with the ultimate goal of separating oneself from others. increase. Various studies have focused on the importance of a solid personal brand, but generally overlooked how to create it in a virtual world, especially for an educator in the current era of digital technology. The purpose of this paper is to explore the different typefaces of different committees and explore the importance of building a personal brand for everyone.